Suicidal tendencies in patients with mental disorders - Gryshko, Дарія; Otroshchenko, Наталія (Psychosomatic Medicine and General Practice, 2026)
Relevance. The relevance of this article is determined by the increasing prevalence of suicidal tendencies worldwide, and particularly in Ukraine. It also depends on the lack of development of psychological and psychiatric support for patients with mental disorders exhibiting these tendencies. There is an acute need for the improvement of methods of early diagnosis and the design of effective programs aimed at prevention of suicidal trends in patients with mental disorders. Aim. The definition of directions for improving psychological and psychiatric support for psychiatric patients with suicidal tendencies through the analysis of studies into the indicated problems. Materials and methods. The study involved the systematization, analysis, and synthesis of the literature on the topic of suicidal tendencies in patients with mental illnesses. The sources were obtained from scientific databases such as PubMed, PsycINFO, Scopus, and Google Scholar. Discussion. The most recent studies have identified a significant increase in the risk of suicide and overall mortality among patients with bipolar disorder, unipolar depression, schizophrenia and other psychiatric conditions. These results highlight the necessity of early identification of high-risk groups and the implementation of systematic preventive measures in psychiatric practice. The literature review demonstrates a significant increase in the risk of developing suicidal tendencies, such as severe symptoms of depression, anxiety, impaired impulse control, maladaptation, and difficulties in social interaction. Our own observations also revealed that combination of affective fluctuations and social isolation often contributes to the formation of suicide risk even in the absence of psychotic symptoms. Effective directions may include social adaptation programs after inpatient treatment, psychoeducational support for families, regular psychological and psychiatric monitoring suicidal tendencies, and the establishment of rapid-response crisis services. Conclusions. The analysis of the literature confirms the considerable prevalence of suicidal tendencies among patients with mental disorders, particularly in context of the ongoing war in Ukraine. It also highlights the insufficient development of diagnostic and preventive measures, the need for further research on this pressing issue, and importance of improving of implementing governmental programs for psychological and psychiatric support for the affected patients. Keywords: suicidal tendencies, mental disorders, diagnosis, prevention, psychological and psychiatric care.